THE INFLUENCE OF ECONOMIC CRISES ON ENTREPRENEURSHIP IN RUSSIA - A. P. Egorshin; I. O. Korobejnikov; N. T. Savrukov (Модернизация, инновация, развитие)
The article is devoted to the analysis of the influence of economic crisis on big, medium and small business in Russia. It shows the dynamics of small business development from 1996 to 2010. It shows current indicators of small business development in Russia as compared with leadingworld economies.